2022
DOI: 10.1021/acsami.2c08335
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Stimuli-Responsive Synapse Based on Vertical van der Waals Heterostructures

Abstract: Brain-inspired intelligent systems demand diverse neuromorphic devices beyond simple functionalities. Merging biomimetic sensing with weight-updating capabilities in artificial synaptic devices represents one of the key research focuses. Here, we report a multiresponsive synapse device that integrates synaptic and optical-sensing functions. The device adopts vertically stacked graphene/h-BN/WSe2 heterostructures, including an ultrahigh-mobility readout layer, a weight-control layer, and a dual-stimuli-responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…S2, † indicating the existence of defect levels. 22 With an increase in carbon doping density, the color of the h-BN crystals becomes deeper yellow (Fig. S2 †), further confirming the introduction of carbon during the growth process.…”
Section: Resultsmentioning
confidence: 69%
“…S2, † indicating the existence of defect levels. 22 With an increase in carbon doping density, the color of the h-BN crystals becomes deeper yellow (Fig. S2 †), further confirming the introduction of carbon during the growth process.…”
Section: Resultsmentioning
confidence: 69%
“…38 Among them, PPF is one of the typical forms of STP, which plays an indispensable role in the realization of nervous system functions and is considered to be the key factor for biological synaptic information processing. 39 The typical PPF behavior was successfully simulated, as shown in Figure 3c. After the irradiation of 532 nm light with a light intensity of 6.99 mW cm −2 for 2 s, a single EPSC behavior appeared.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…STP is a transient synaptic weight modulation process in which EPSC lasts only hundreds to thousands of milliseconds and then returns to the initial state . Among them, PPF is one of the typical forms of STP, which plays an indispensable role in the realization of nervous system functions and is considered to be the key factor for biological synaptic information processing . The typical PPF behavior was successfully simulated, as shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that current synaptic devices have potential applications in direction recognition. In addition, 2D materials are usually used as charge-trapping layers in synaptic devices. , For instance, Zhou et al reported a 2D van der Waals heterojunction synaptic transistor, which was based on the structure of graphene/h-BN/WSe 2 (Figure d) . Graphene served as the p-type channel, and h-BN was used as the charge-trapping layer.…”
Section: Synaptic Devices Based On 2d Materialsmentioning
confidence: 99%
“…(f) The mimicked LTP/LTD based on graphene/h-BN/WSe 2 synaptic device. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Synaptic Devices Based On 2d Materialsmentioning
confidence: 99%